2010
DOI: 10.1073/pnas.1016234107
|View full text |Cite
|
Sign up to set email alerts
|

Malignant cells facilitate lung metastasis by bringing their own soil

Abstract: Metastatic cancer cells (seeds) preferentially grow in the secondary sites with a permissive microenvironment (soil). We show that the metastatic cells can bring their own soil-stromal components including activated fibroblasts-from the primary site to the lungs. By analyzing the efferent blood from tumors, we found that viability of circulating metastatic cancer cells is higher if they are incorporated in heterotypic tumor-stroma cell fragments. Moreover, we show that these cotraveling stromal cells provide a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
423
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 510 publications
(451 citation statements)
references
References 21 publications
12
423
1
1
Order By: Relevance
“…Loss of pericytes from tumor vessels may either permit tumor cell intravasation and PFT or hijack tumor cells for intravasation, and perhaps even the formation of the initial metastatic niches in distal tissues and organs. Indeed, it has been described that tumors can carry their own fibroblasts as "soil" for them to "seed" and grow in distal organs (42). Therefore, pericytes play dynamic roles in cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Loss of pericytes from tumor vessels may either permit tumor cell intravasation and PFT or hijack tumor cells for intravasation, and perhaps even the formation of the initial metastatic niches in distal tissues and organs. Indeed, it has been described that tumors can carry their own fibroblasts as "soil" for them to "seed" and grow in distal organs (42). Therefore, pericytes play dynamic roles in cancer invasion and metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, some of the early signalling that contributes to pre-metastatic niche formation may originate from passenger fibroblasts, accompanying the disseminating tumour cells to the secondary site. Support for this comes from two recent reports demonstrating that metastatic Lewis lung carcinoma cells and human pancreatic cancer cells provide their own stromal components, including activated fibroblasts, from primary sites to the metastatic organs [111].…”
Section: Cafs Modulate the Metastatic Nichementioning
confidence: 99%
“…41,42 Moreover, CTCs appear to contain clusters of heterogeneous cell populations composed of platelets, leukocytes and mesenchymal cells. [43][44][45] The half-life of CTCs in the circulation is short, i.e., measured in hours, which is partially related to their fast clearance from the circulation and/or apoptosis. 46 To date, whether CTCs and DTCs extracted from either patients or mouse tumor models are capable of forming metastases when introduced into recipient mice has not been shown.…”
Section: Tumor Cell-autonomous Alterations Influencing Metastasismentioning
confidence: 99%
“…Sampling of the blood from these mice when tumors reached approximately 10 mm in diameter showed that 80% of isolated ds-Red+ CTCs traveled as single cells, while some ds-Red+CTCs formed clusters containing viable GFP + host stromal cells. 44 In addition, mice having GFP + cells specifically in their skin were generated by the parabiosis skin transplantation and ds-Red + macrophages (28%). Furthermore, human mammary CAFs were injected subcutaneously together with murine LLC1 cells into recipient mice and allowed to metastasize with carcinoma cells into the lung.…”
Section: Metastasis-promoting Signal From the Tumor-associated Stromamentioning
confidence: 99%
See 1 more Smart Citation